Development Of Critical Thinking Skills In Mathematics - Irawati, Endang (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Mathematics lessons are considered by most students to be difficult, making it a challenge for a teacher to change this statement. To overcome this, critical thinking skills were developed to overcome these problems. Development of Critical Thinking Skills includes several indicators and stages. Indicators of critical thinking skills include: Delivering simple explanations, Developing basic skills, Providing conclusions, Providing further explanations, and Being able to design strategies and tactics. The stages in critical thinking skills consist of analyzing, synthesizing, recognizing and solving problems, concluding, and evaluating and assessing.